2019
DOI: 10.1080/08874417.2018.1564632
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Logics and Their Influence on Enterprise Architecture Adoption

Abstract: Enterprise architecture adoption (EAA), often ironically known as "ineffective adoption," is frequently marked by poor utilization and signals of failure. To date, comprehensive examinations of which factors influence EAA are lacking. This study aims to address this knowledge gap. The paper uses an interpretive multiple case-study approach using an institutional theory lens to conduct the research. The findings show that three institutional logics dominate EAA: managerialism, professionalism, and user logic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In that sense, EA project and its activities can be understood to be a part of EAM. EA products are outputs of an EA project, such as strategic plans, standards, and frameworks (Dang 2019). EA approach is understood as methodologies to establish an EA.…”
Section: Enterprise Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…In that sense, EA project and its activities can be understood to be a part of EAM. EA products are outputs of an EA project, such as strategic plans, standards, and frameworks (Dang 2019). EA approach is understood as methodologies to establish an EA.…”
Section: Enterprise Architecturementioning
confidence: 99%
“…Second, although institutional theory is used in the EA literature, the theory is used to study on the barriers of institutionalization (Iyamu 2009), interoperability challenges (Hjort-Madsen and Gøtze 2004), governmental pressures (Hjort-Madsen, 2007), or institutional logics within EA adoption (Dang 2019). These studies have not revealed how individuals and groups are involved in or are influenced by the pressure.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of this approach is its alignment with other IS or strategies. For example, the MRP was designed within the country's enterprise architectural framework [38]. In that sense, the platform can easily harmonize with other systems at different levels of administrative systems, from the central government (e.g., the Ministry of Health), local governments, and counties to the municipalities.…”
Section: Approaches To Establishing National Ehealth Platformsmentioning
confidence: 99%
“…Various IS studies have also used the competing institutional logics perspective, e.g., to examine enterprise information system implementation [32,39], independent third-party app development [40], enterprise architecture adoption [41], digital infrastructure [42], and digital innovation [43].…”
Section: Theoretical Background 31 Institutional Logicsmentioning
confidence: 99%